A new genus and species of Apseudidae, and a new species of Bunakenia (Crustacea: Tanaidacea: Apseudomorpha) from the Northwest Atlantic and Gulf of Mexico - Drumm, David T.; Heard, Richard W. (Zootaxa, 2022)
Examination of material from the Campeche region of the southern Gulf of Mexico revealed the presence of a new genus and species of Apseudidae that appears to be transitional between Bunakenia Guţu and Apseudes Leach sensu lato. This new taxon, Pseudobunakenia anablesis n. gen., n. sp. is found throughout the Gulf of Mexico (GOM) and Northwest Atlantic as far north as South Carolina. It is known in the literature under the designation “Apseudes spinosa” Sars sensu Dawson and “Apseudes sp. A” (Heard et al.). Also, Bunakenia hamata n. sp. is described from offshore Georgia and is distributed from the Florida Gulf Coast and the Northwest Atlantic as far north as South Carolina. It is known in the literature under the designation “Bunakenia sp. A” (Heard et al.) and is the only known species of that genus in the GOM/NW Atlantic. It can be distinguished from its congeners by a combination of characters such as the pereonites having posterolateral apophyses, the antennule first peduncle article denticulate, the antennule accessory flagellum having five articles, and the first pereopod having four ventral propodal spiniform setae. A key to the known species is presented.